Study of rheology and plug assist thermoforming of linear and branched pp homopolymer and impact copolymer - Marathe, D.; Shelar, S.; Mahajan, S.; Ahmad, Z.; Gupta, S.; Kulkarni, S.; Juvekar, V; Lele, A. (International Polymer Processing, 2019)
Polypropylene (PP) is one of the fastest growing thermoplastic polymers in the world, second only to polyethylene. This is primarily due to its excellent balance of physical and chemical properties at a lower cost. PP however possesses low melt strength on account of its linear structure and hence is not easily amenable to processing techniques that involve free surface stretching deformations like thermoforming, blow molding and extrusion film casting. One way to enhance the melt strength of PP is to incorporate long chain branches in its molecular architecture. The present study focuses on the impact of rheology of linear and branched PP on their thermoforming characteristics. Two grades each of linear and long chain branched (LCB) PP homopolymer and impact copolymer (ICP) were used. It was observed that the LCB-PP homopolymer and LCB-ICP showed higher flow activation energy, reduced value of loss tangent and nearly equal frequency dependence of storage and loss moduli in shear rheology. Also, a strong strain hardening behavior was displayed in extensional rheology by the LCB grades. Plug assist thermoforming experiments were carried out to assess the effect of long chain branching on surface strain and thickness distribution for axisymmetric cups of two draw ratios. Biaxial surface strain maps of the formed cups were quantified using Grid Strain Analysis (GSA). Thermoformed cups made from LCB-PP homopolymer and LCB-impact copolymer showed lower surface strain and overall higher thickness as compared to cups made from their linear counterparts, which is in accordance with what might be expected from their rheology.